Exploring Students' Perception toward the Implementation of Sci-summary to improve Writing Skills - Fajaria, Nurul Hasanah; Gunawan, Agus; Fadhil, Muhammad Rizky; Amanda, Hana (Akademika : Jurnal Teknologi Pendidikan, 2025)
The ability to write effectively is a fundamental academic skill for university students, yet many continue to face challenges in understanding complex texts, organizing ideas, and applying appropriate academic language. In response to these challenges, artificial intelligence (AI) tools such as SciSummary have emerged, offering automated summaries of scientific articles to aid comprehension and support writing development. This study aims to explore students’ perceptions of SciSummary, its impact on their academic writing processes, and their attitudes toward AI-assisted learning. Using a quantitative approach, the study employed a close-ended questionnaire distributed to 48 English Education students at Universitas Islam As-Syafi’iyah who had used SciSummary in their academic writing assignments. Data were analyzed through scoring, descriptive statistics, and visualization. The results reveal a generally positive perception of SciSummary. Students agreed that the tool helps them better understand academic texts (mean score 4.4), increases reading efficiency (4.3), and assists in learning vocabulary and writing structures (4.2). Furthermore, SciSummary supports students in generating ideas (4.3), structuring texts (4.4), and increasing writing confidence (4.5). Attitudinal responses also showed strong agreement on the importance of integrating AI tools into writing courses (4.6), although some concerns about over-reliance on technology (3.0) and academic dishonesty (2.8) were noted. In conclusion, SciSummary is seen as a helpful AI tool that contributes positively to students’ comprehension and writing skills. Nevertheless, its use should be guided to ensure ethical practices and to prevent excessive dependence. The study recommends further research with a larger sample and over a longer period to better understand the long-term effects of AI-assisted writing.